ANTINOMI KONSTITUSI: TRANSISI MASA JABATAN DAN QUO VADIS PEMILU PASCA PUTUSAN MAHKAMAH KONSTITUSI No. 135/PUU-XXII/2024 - Adhe Ismail Ananda; La Ode Dedihasriadi (Dialogia Iuridica, 2026)
The Constitutional Court's Decision No. 135/PUU-XXII/2024 marks a fundamental reformulation of the design of election synchronization in Indonesia. The separation between the national and regional elections ordered by the Court opens up space for the rearrangement of the electoral system in a more functional direction, but at the same time creates new tensions in terms of term of office and power transition scheme. This article analyzes the constitutional implications of the ruling using a normative juridical research method, which relies on the legislative approach and the Constitutional Court's ruling. The discussion focused on two main aspects: first, the tension between the Constitutional Court's decision and the constitutional provisions related to the term of office; Second, the draft of a legitimate and legitimate transition of power, including the idea of a "limited extension with constitutional basis." This study shows that the implementation of the Constitutional Court's decision must be differentiated based on the normative sources of public office, and that the transitional design must uphold the supremacy of the constitution and the principles of electoral democracy. Without the prudence of legal design, the potential for power engineering will overshadow this post-verdict democratization process.